A surrogate thermal modeling and parametric optimization of battery pack with air cooling for EVs. (25th January 2019) - Li, Wei; Xiao, Mi; Peng, Xiongbin; Garg, Akhil; Gao, Liang
Highlights: Surrogate thermal models and optimization to improve air cooling performance. Optimized battery pack behaves better cooling effect and occupies less space. Easily applied methodology for industrial battery pack with hundreds of cells. Abstract: The battery packs in electric vehicles usually operate at high current discharge rates which leads to the higher heat generation. This may have safety issues and negative impact on the battery performance over the period. Existing researches focused more on the configurations and design of battery cells/modules arrangements to reduce the maximum temperature rise of the battery pack. However, temperature differences are more important and difficult to manage. It is also known that smaller the size of the battery pack, higher the space can be saved. This article proposes a comprehensive methodology to design an efficient air-cooling system, which is hybrid of system volume and cooling performance. The proposed methodology comprises of the four steps: the design of air cooling battery, setup of the computational fluid dynamics codes, design of experiments (DoE), evaluation and selection of surrogate models. These models are then optimized using the multi-objective optimization approach for the selection of optimum scheme for air cooling battery module. The optimization results show that the optimized air cooling battery module has higher thermal performance. The proposed methodology will be useful for industrial battery pack design process to reduce maximum temperature, temperature difference and the volume of battery pack.